A Study Of Work-Life Balance And Its Impact On Employees In SBI And ICICI Bank (International Journal of Innovative Research in Engineering & Management, 2022)
Over the last few years, life has changed  for everyone. The COVID-19 pandemic has taken many  lives, changed working patterns, and introduced a new  normal in our lives. The new normal has introduced work  from home, social distancing, alternate working hours, and  much more. Employees’ expectations of their job have  been changed. The mindset of family life after retirement  has perished. Uncertainty of life has suggested that family  life is as important as a career. People now don’t look for  jobs that are high paying but they are seeking a balance.  The present study is an effort to understand the work-life  balance among bank employees. Researchers have  surveyed SBI and ICICI employees to know their work-life  balance status among them. The present study finds the  contemporary work-life balance in public and private  sector banks in India. The finding of the research suggests  that work-life balance is not so good among bank  employees. Though there are some advantages in public  sector banks and a few others in private sector banks  overall employees need reform at both ends.
Keywords: Banking work culture; Work-Life balance; New Labour Codes